Determinants of Corporate Social Responsibility in Japanese Companies - Magdalena Krukowska (Management and Business Administration. Central Europe, 2014)
Purpose: The aim of this study was to analyze the factors that determine the Japanese approach to corporate social responsibility (CSR) to facilitate future empirical research in the Polish conditions. Methodology: To conduct the research, the available literature concerning CSR, managerial behaviour and stakeholder relations in Japan was studied. The research was conducted onsite in Japan after consultation with local experts, both Japanese and foreigners, specialized in Japanese management and the economy. Findings: The Japanese approach to CSR is strongly determined by their religious, philosophical, cultural, historical, economic and legal factors. It is proof of the concept of CSR contextuality, which provokes questions about the nature of the business relations of Japanese companies with their foreign counterparts and their style of management while investing abroad. Research limitations: The methodology was only supposed to gain a general view of the factors infl uencing CSR in Japan. Studying more detailed issues with the use of empirical data was complicated because of the short time available for the research (6 weeks) and the relatively low level of transparency of the Japanese companies. Value: The study helped in understanding managerial decisions and Japanese business behaviour in the context of corporate responsibility and the ethics of its everyday operations. It was the fi rst research thoroughly analyzing many of the determinants of CSR in Japan, which may be valuable for any counterparts cooperating with the Japanese companies and foreign researchers analyzing Japanese management systems.